2015
DOI: 10.1007/s11032-015-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of agronomic and quality traits in USDA pea single-plant collection

Abstract: Association mapping is an efficient approach for the identification of the molecular basis of agronomic traits in crop plants. For this purpose in pea (Pisum sativum L.), we genotyped and phenotyped individual lines of the single-plant-derived core collection of the USDA pea collection including accessions from 330 landraces and cultivars of Pisum var. pumilio, three P. abyssinicum, two P. fulvum, and one P. sativum subsp. transcaucasicum. These 384 accessions were collected or donated from a total of 64 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…In case of linseed different types of DNA based markers includingAFLP,RAPD,retrotransposon,ISSR,SSRs,SNPetc. havebeenusedforevaluatingthegenetic diversityandlinkage mapping (Cloutier et al 2010;Oh et al 2000;Spielmeyer et al 1998).OverothertypesofDNAmarkers,SSRsarewidelyused forgeneticdiversityandstructureanalysisinseveralcropplants (Cheng et al 2015;Yan et al 2009;Cane et al 2014;Cui et al 2013). In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of linseed different types of DNA based markers includingAFLP,RAPD,retrotransposon,ISSR,SSRs,SNPetc. havebeenusedforevaluatingthegenetic diversityandlinkage mapping (Cloutier et al 2010;Oh et al 2000;Spielmeyer et al 1998).OverothertypesofDNAmarkers,SSRsarewidelyused forgeneticdiversityandstructureanalysisinseveralcropplants (Cheng et al 2015;Yan et al 2009;Cane et al 2014;Cui et al 2013). In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Association mapping is widely being utilized for detecting marker-trait association based on the genetic resources routinely used for genetic improvement programs (Font I Forcada et al 2015;Cheng et al 2015;Yan et al 2009;Cai et al 2013). As compared to biparental QTL mapping, association mapping increases the range of natural variation that can be exploited in a single experiment and potential genomic regions could be identified (Jin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…association studies but are still limited in number and polymorphism (Cheng et al, 2015;Diapari et al, 2015). Single nucleotide polymorphism markers at present are therefore of less use than SSRs for germplasm studies.…”
mentioning
confidence: 99%
“…The USDA core collection has also been evaluated for yield components (McPhee and Muehlbauer, 2001), mineral nutrients (Grusak et al, 2004), and seed protein content (Coyne et al, 2005). In a later study, 256 SNP markers were used to group pea accessions and identify marker ÂŽ trait associations with 25 traits measured on single-plant-derived lines from this same collection (Cheng et al, 2015). In a later study, 256 SNP markers were used to group pea accessions and identify marker ÂŽ trait associations with 25 traits measured on single-plant-derived lines from this same collection (Cheng et al, 2015).…”
mentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNP) have now become the preferred markers due to their abundance and uniform distribution throughout genomes (Gupta et al 2008), as confirmed by molecular linkage maps produced by Aubert et al (2006), Deulvot et al (2010), Duarte et al (2014) and Sindhu et al (2014). However, investigations on the linkage of SNP markers with pea production, phenology or grain quality traits are relatively few (Timmerman-Vaughan et al 2005;Burstin et al 2007;Klein et al 2014;Cheng et al 2015;Jha et al 2015), and the QTL ability to explain sufficient phenotypic variation for use in MAS is controversial. One reason for that is the complex and polygenic control of most of these traits, which results in only moderate cumulative QTL effect (Tar'an et al 2004;Burstin et al 2007;Klein et al 2014).…”
mentioning
confidence: 99%